A Novel Configuration of A Microstrip Power Amplifier based on GaAs-FET for ISM Applications - Amine Rachakh; Larbi El Abdellaoui; Jamal Zbitou; Ahmed Errkik; Abdelali Tajmouati; Mohamed Latrach (Institute of Advanced Engineering and Science, 2018)
Power Amplifiers (PA) are very indispensable components in the design of numerous types of communication transmitters employed in microwave technology. The methodology is exemplified through the design of a 2.45GHz microwave power Amplifier (PA) for the industrial, scientific and medical (ISM) applications using microstrip technology. The main design target is to get a maximum power gain while simultaneously achieving a maximum output power through presenting the optimum impedance which is characteristically carried out per adding a matching circuit between the source and the input of the power amplifier and between the load and the output of the power amplifier. A